2008
DOI: 10.1007/s00345-008-0350-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of non-papillary tumor morphology as a predictor of cancer progression and survival in patients with primary T1G3 bladder cancer

Abstract: Non-papillary tumor morphology was a predictor of cancer progression and survival in patients with primary T1G3 BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…As reported previously, once progression to invasive cancer (pT2‐4) occurs, the median survival rate is just 12–15 months, and this has not been improved over the past two decades, despite the development and use of different chemotherapeutic treatment approaches 18 . Therefore, identification of prognostic clinicopathological factors, especially in relation to tumor recurrence and progression, is crucial to manage UC optimally 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously, once progression to invasive cancer (pT2‐4) occurs, the median survival rate is just 12–15 months, and this has not been improved over the past two decades, despite the development and use of different chemotherapeutic treatment approaches 18 . Therefore, identification of prognostic clinicopathological factors, especially in relation to tumor recurrence and progression, is crucial to manage UC optimally 19 …”
Section: Discussionmentioning
confidence: 99%
“…18 Therefore, identification of prognostic clinicopathological factors, especially in relation to tumor recurrence and progression, is crucial to manage UC optimally. 19 Although tumor grade and stage are the most accurate prognostic factors in the evaluation of bladder UC, they cannot always predict the true tumor biological potential, as non-muscle invasive tumors of the same stage and grade can have completely different clinical courses. 4 Furthermore, non-muscle invasive UC is a heterogeneous spectrum of diseases with different biological and clinical behaviors, determined by distinct molecular alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Okajima et al (11) reported that patients with non-papillary tumors had significantly worse CSS than did patients with papillary tumors. Park et al (12) reported that non-papillary tumors were associated with the presence of lymphovascular invasion and CIS. Additionally, other reports showed that lymphovascular invasion was an independent prognostic factor for T1 bladder cancer (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Transurethral resection of the bladder (TURB) was performed with curative intent by 2 surgeons (H.A and C.S.K), and our detailed TURB technique was addressed in a prior study [12]. All patients received intravesical BCG therapy consisting of 6 weekly instillations of oncotice strain BCG (12.5 mg in 50 ml saline) within 2ϳ4 weeks after surgery.…”
Section: Patient Populationmentioning
confidence: 99%
“…Prior studies have suggested that several clinicopathologic parameters, such as tumor size [10,11], multiplicity [10], morphology [12], concomitant carcinoma-in-situ (CIS) [10,11], and response to intravesical therapy [13] are risk factors for tumor progression and patient mortality in T1G3 BC. However, the results of these studies are inconsistent; meanwhile, some studies found no prognostic value of such clinicopathologic parameters in T1G3 BC [14].…”
Section: Introductionmentioning
confidence: 99%